THE USE OF AUTHENTIC MATERIALS IN STUDENTS’ READING COMPREHENSION OF LOW AND HIGH PROFICIENCY LEVELS - Maratul Azizah Nanang Jayani (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2023)
The aim of this study were to find out whether there was significant difference of students who were taught through authentic material, the aspects of reading skills that almost influenced by the student in reading comprehension through authentic material and the last was to see students’ perceptions of teaching and learning through authentic material. This research was used authentic material in reading comprehension of students’ of low and high proficiency levels. This research was quantitative research which consists of one group pre-test and post-test design. The result of T-test Sig. (2 tailed) showed that there was significant difference between high and low proficiency level students. Then finding of inference aspect of the reading that almost influenced reading comprehension in high proficiency level students while finding supporting details the aspects that mostly influenced in low proficiency level students. In addition, the high level proficiency level and low proficiency level students have a positive perception in teaching and learning through authentic material.  Finding inference was the aspect of reading that mostly influenced reading comprehension in high proficiency level students while finding supporting details was the aspect that mostly   influenced in low proficiency level students. Moreover, the high proficiency level and low proficiency level students have a positive perception in teaching and learning through authentic material.